Ferritic alloys
By adjusting the Cr, Si and Al content relationship in ferrite alloy, the problem that the alloy is difficult to form a protective oxide layer at low temperature is solved, and excellent oxidation resistance and ductility are achieved, and it is suitable for high-temperature corrosion environments.
Patent Information
- Application Number
- CN201780024611.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-04-22
- Filing Date
- 2017-03-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2037-03-06
AI Technical Summary
It is difficult for the existing ferrite alloy to form a protective α-alumina layer at a temperature below 900°C, resulting in problems of corrosion erosion and oxidative instability.
By adjusting the composition of the alloy, it is ensured that the contents of Cr, Si and Al meet a specific relationship (0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022) is met to promote the formation of a protective surface layer with an aluminum-rich oxide.
An alloy with excellent oxidation resistance and ductility at a temperature below 900°C is achieved, which reduces brittleness and increases high temperature corrosion resistance.
Smart Images

Figure BDA0001834538380000101 
Figure BDA0001834538380000111 
Figure FDF0000029482150000011
Abstract
Description
Technical Field
[0001] The present disclosure relates to a ferritic alloy according to the preamble of claim 1. The present disclosure also relates to the use of the ferritic alloy and to articles or coatings produced therefrom. Background Art
[0002] Ferritic alloys, such as FeCrAl alloys containing chromium (Cr) levels of 15-25 wt. % and aluminum (Al) levels of 3-6 wt. %, are well known for their ability to form a protective alpha-alumina (Al2O3), aluminum oxide layer when exposed to temperatures between 900 and 1300° C. The lower limit of Al content to form and maintain the aluminum oxide layer varies with exposure conditions. However, at higher temperatures, the effect of too low Al levels is that the selective oxidation of Al will fail and a less stable and less protective chromium and iron based oxide layer will form.
[0003] It is generally believed that FeCrAl alloys will not normally form a protective alpha-alumina layer if exposed to temperatures below about 900° C. Attempts have been made to optimize the composition of FeCrAl alloys so that protective alpha-alumina will form at temperatures below about 900° C. However, in general these attempts have not been very successful because the diffusion of oxygen and aluminum to the oxide-metal interface is relatively slow at lower temperatures and the rate of formation of the aluminum oxide layer is low, which means that there will be a risk of severe corrosive attack and the formation of a less stable oxide.
[0004] Another problem that arises at lower temperatures, i.e., temperatures below 900°C, is the phenomenon of long-term embrittlement caused by the low temperature miscibility gap of Cr in the FeCrAl alloy system. At 550°C, a miscibility gap exists for Cr levels above about 12 wt. %. Recently, alloys with lower Cr levels of about 10-12 wt. % Cr have been developed to avoid this phenomenon. This group of alloys has been found to perform very well in molten lead under controlled and low pressure O2.
[0005] EP 0 475 420 relates to a rapidly solidified ferritic alloy foil consisting essentially of: Cr, Al, about 1.5-3 wt. % Si, and REM (Y, Ce, La, Pr, Nd), the balance being Fe and impurities. The foil may also contain about 0.001-0.5 wt. % of at least one element selected from Ti, Nb, Zr and V. The foil has a grain size of no greater than about 10 μm. EP 075 420 discusses the addition of Si to improve the flow characteristics of the alloy melt, but with limited success due to reduced ductility.
[0006] EP 0091 526 relates to alloys that are resistant to heat cycle oxidation and are hot workable, more specifically to iron-chromium-aluminium alloys with rare earth additions. In oxidation, the alloys will produce the whisker texture oxides that are desirable on the surface of catalytic converters. However, the resulting alloys do not provide high temperature resistance.
[0007] Therefore, there is still a need to further improve the corrosion resistance of ferritic alloys so that they can be used in corrosive environments during high temperature conditions. An aspect of the present disclosure is to solve or at least reduce the above problems. Summary of the invention
[0008] Thus, the present disclosure is directed to a ferritic alloy that will provide a combination of good oxidation resistance and excellent ductility, the ferritic alloy comprising the following composition in weight % (wt %):
[0009] C 0.01 to 0.1;
[0010] N: 0.001-0.1;
[0011] O: ≤0.2;
[0012] Cr 4 to 15;
[0013] Al 2 to 6;
[0014] Si 0.5 to 3;
[0015] Mn: ≤0.4;
[0016] Mo+W≤4;
[0017] Y≤1.0;
[0018] Sc, Ce and / or La≤0.2;
[0019] Zr≤0.40;
[0020] RE≤1.0;
[0021] The balance is Fe and normally occurring impurities and must also satisfy the following equation:
[0022] 0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022.
[0023] Thus, there is a relationship between the contents of Cr and Si and Al in the alloy according to the present disclosure, which, if satisfied, will provide an alloy having excellent oxidation resistance and ductility as well as reduced brittleness and increased high temperature corrosion resistance.
[0024] The present disclosure also relates to an article and / or a coating comprising the ferritic alloy according to the present disclosure.In addition, the present disclosure also relates to the use of the ferritic alloy as defined above or below for the manufacture of an article and / or a coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1a and Figure 1b Disclosed is Fe-10%Cr-5%Al( Figure 1a ) and Fe-20%Cr-5%Al ( Figure 1b ) in the phase. This figure was created by using the database TCFE7 and the Thermocalc software.
[0026] Figure 2a to Figure 2e Polished cross-sections of two alloys according to the present disclosure and three reference alloys after contact with biomass (wood chips) ash containing a large amount of potassium at 850° C. for 50 one-hour cycles are disclosed. DETAILED DESCRIPTION
[0027] As described above, the present disclosure provides a ferrite alloy, the ferrite alloy comprising, in weight % (wt %):
[0028] C 0.01 to 0.1;
[0029] N: 0.001-0.1;
[0030] O: ≤0.2;
[0031] Cr 4 to 15;
[0032] Al 2 to 6;
[0033] Si 0.5 to 3;
[0034] Mn: ≤0.4;
[0035] Mo+W≤4;
[0036] Y≤1.0;
[0037] Sc, Ce and / or La≤0.2;
[0038] Zr≤0.40;
[0039] RE≤1.0;
[0040] The balance is Fe and normally occurring impurities and must also satisfy the following equation:
[0041] 0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022.
[0042] It has been surprisingly found that alloys as defined above or below, i.e. alloys containing alloying elements and within the ranges mentioned herein, unexpectedly form a protective surface layer containing aluminum-rich oxides even when the chromium level is as low as 4% by weight. This is very important for the workability and long-term phase stability of the alloy, because after being placed in a temperature environment in the range mentioned herein for a long time, the undesirable brittle σ phase will be reduced or even avoided. Therefore, the interaction between Si and Al and Cr will promote the formation of a stable and continuous protective surface layer containing aluminum-rich oxides, and by using the above equation, Si will be added and still obtain a ferritic alloy that will produce and form different products. The inventors have surprisingly found that if the amounts of Si and Al and Cr are balanced so that the following conditions are met (all numbers of elements are weight fractions):
[0043] 0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022,
[0044] The resulting alloy will then have a combination of excellent oxidation resistance and workability and formability within the Cr range of the present disclosure. According to one embodiment, 0.015≤(Al+0.5Si)(Cr+10Si+0.1)≤0.021, such as 0.016≤(Al+0.5Si)(Cr+10Si+0.1)≤0.020, such as 0.017≤(Al+0.5Si)(Cr+10Si+0.1)≤0.019.
[0045] The ferritic alloys of the present disclosure are particularly useful at temperatures below about 900°C, since a protective surface layer containing aluminum-rich oxides will be formed on articles and / or coatings made from the alloys, which will prevent corrosion, oxidation, and embrittlement of the articles and / or coatings. In addition, the ferritic alloys of the present invention can provide protection against corrosion, oxidation, and embrittlement at temperatures as low as 400°C, since a protective surface layer containing aluminum-rich oxides will be formed on the surface of articles and / or coatings made therefrom. In addition, the alloys according to the present disclosure will also perform well at temperatures up to about 1100°C, and they show a reduced tendency to long-term embrittlement in the temperature range of 400 to 600°C.
[0046] The alloy of the present invention can be used in the form of a coating. In addition, articles may also include the alloy of the present invention. According to the present disclosure, the term "coating" is intended to refer to the following embodiments, wherein the ferritic alloy according to the present disclosure is present in the form of a layer, which is placed in a corrosive environment in contact with a substrate, regardless of the means and methods for achieving it, and regardless of the relative thickness relationship between the layer and the substrate. Therefore, examples thereof are, but are not limited to, PVD coatings, overlays, or composites or composite materials. The purpose of the alloy should be to protect the underlying material from corrosion and oxidation. Examples of suitable articles are, but are not limited to, composite pipes, pipes, boilers, gas turbine components, and steam turbine components. Other examples include superheaters, water-cooled walls in power plants, components in containers or heat exchangers (e.g., for reforming or other treatment of hydrocarbons or gases containing CO / CO2), components used in industrial heat treatment of steel and aluminum, powder metallurgy processes, and gas and electric heating elements.
[0047] In addition, the alloys according to the present disclosure are suitable for use in environments with corrosive conditions. Examples of such environments include, but are not limited to, contact with salts, liquid lead and other metals, contact with ash or high carbon content deposits, combustion atmospheres, atmospheres with low pO2 and / or high N2, and / or high carbon activity environments.
[0048] In addition, the ferritic alloys of the present invention can be made using solidification rates that normally occur in the range from conventional metallurgy to rapid solidification. The alloys of the present invention are also suitable for making all types of forged and extruded products, such as wire, strip, rod and plate. The amount of hot and cold plastic deformation, as well as the grain structure and grain size, vary between product forms and production routes as known to those skilled in the art.
[0049] The functions and effects of the essential alloying elements of the alloys defined above and below will be presented in the following paragraphs.The list of functions and effects of the individual alloying elements should not be considered complete, as other functions and effects may also exist for the alloying elements.
[0050] Carbon (C)
[0051] Carbon may be present as an unavoidable impurity resulting from the production process. Carbon may also be included in ferritic alloys as defined above or below to improve strength by precipitation hardening. In order to have a significant effect on the strength of the alloy, carbon should be present in an amount of at least 0.01% by weight. At too high a level, carbon may result in difficulty in forming the material and also have a negative effect on corrosion resistance. Therefore, the maximum amount of carbon is 0.1% by weight. For example, the content of carbon is 0.02-0.09% by weight, such as 0.02-0.08% by weight, such as 0.02-0.07% by weight, such as 0.02-0.06% by weight, such as 0.02-0.05% by weight, such as 0.01-0.04% by weight.
[0052] Nitrogen (N)
[0053] Nitrogen may be present as an unavoidable impurity resulting from the production process. Nitrogen may also be included in ferritic alloys as defined above or below to improve strength by precipitation hardening, particularly when a powder metallurgy process route is applied. At too high a level, nitrogen may result in difficulty in alloy formation and also have a negative effect on corrosion resistance. Therefore, the maximum amount of nitrogen is 0.1 wt %. Suitable nitrogen ranges are, for example, 0.001-0.08 wt %, such as 0.001-0.05 wt %, such as 0.001-0.04 wt %, such as 0.001-0.03 wt %, such as 0.001-0.02 wt %.
[0054] Oxygen (O)
[0055] Oxygen may be present in the alloy as defined above or below as an impurity resulting from the production process. In such case, the amount of oxygen may be up to 0.02% by weight, for example up to 0.005% by weight. If oxygen is intentionally added to provide strength by dispersion strengthening, the alloy as defined above or below contains up to or equal to 0.2% by weight of oxygen when the alloy is manufactured by a powder metallurgy process route.
[0056] Chromium (Cr)
[0057] Chromium is present mainly as a matrix solid solution element in the alloy of the present invention. Chromium promotes the formation of an aluminum oxide layer on the alloy by the so-called third element effect, i.e., by forming chromium oxide in the transient oxidation stage. To achieve this purpose, chromium should be present in the alloy as defined above or below in an amount of at least 4% by weight. In the alloy of the present invention, Cr also enhances the sensitivity to the formation of brittle σ phase and Cr3Si. This effect occurs at about 12% by weight and is enhanced at levels above 15% by weight, so the limit of Cr is 15% by weight. In addition, from the point of view of oxidation, levels above 15% by weight will result in an undesirable contribution of Cr to the protective oxide oxide layer. According to one embodiment, the content of Cr is 5-13% by weight, such as 5-12% by weight, such as 6-12% by weight, such as 7-11% by weight, such as 8-10% by weight.
[0058] Aluminum (Al)
[0059] Aluminum is an important element in alloys as defined above or below. Aluminum, when exposed to oxygen at high temperatures, forms a dense and thin oxide Al2O3 by selective oxidation, which will protect the underlying alloy surface from further oxidation. The amount of aluminum should be at least 2% by weight to ensure the formation of a protective surface layer containing aluminum-rich oxides, and also to ensure that there is enough aluminum to repair the protective surface layer when it is damaged. However, aluminum has a negative effect on formability, and large amounts of aluminum can lead to cracks forming in the alloy during its machining. Therefore, the amount of aluminum should not exceed 6% by weight. For example, the aluminum can be 3-5% by weight, such as 2.5-4.5% by weight, such as 3-4% by weight.
[0060] Silicon (Si)
[0061] In commercial FeCrAl alloys, silicon is usually present at a level of up to 0.4 wt%. In ferritic alloys as defined above or below, Si will play a very important role, since it has been found that Si has a great effect on improving oxidation resistance and corrosion resistance. The upper limit of Si is set by the loss of workability under hot and cold conditions and the increased sensitivity to the formation of brittle Cr3Si and σ phases during long-term exposure. Therefore, the addition of Si must be carried out in relation to the content of Al and Cr. Therefore, the amount of Si is 0.5-3 wt%, such as 1-3 wt%, such as 1-2.5 wt%, such as 1.5-2.5 wt%.
[0062] Manganese (Mn)
[0063] Manganese may be present as an impurity in an alloy as defined above or below at up to 0.4 wt.-%, for example 0-0.3 wt.-%.
[0064] Yttrium (Y)
[0065] In melt metallurgy, yttrium can be added in an amount of up to 0.3% by weight to improve the adhesion of the protective surface layer. Furthermore, in powder metallurgy, if yttrium is added to produce a dispersion with oxygen and / or nitrogen, the yttrium content is an amount of at least 0.04% by weight to achieve the desired dispersion hardening effect by oxide and / or nitride. The maximum amount of yttrium in a dispersion hardened alloy in the form of an oxygen-containing Y compound can be up to 1.0% by weight.
[0066] Scandium (Sc), cerium (Ce) and lanthanum (La)
[0067] Scandium, cerium and lanthanum are interchangeable elements and may be added individually or in combination in a total amount of up to 0.2 wt. % to improve oxidation properties, self-repairing of aluminum oxide (Al2O3) layers or adhesion between alloys and Al2O3 layers.
[0068] Molybdenum (Mo) and tungsten (W)
[0069] Both molybdenum and tungsten have a positive effect on the hot strength of the alloy as defined above or below. Mo also has a positive effect on the wet corrosion properties. They can be added individually or in combination in an amount of up to 4.0 wt. %, for example 0-2.0 wt. %.
[0070] Reactive Elements (RE)
[0071] By definition, reactive elements are very reactive with carbon, nitrogen and oxygen. Titanium (Ti), niobium (Nb), vanadium (V), hafnium (Hf), tantalum (Ta) and thorium (Th) are reactive elements in the sense of having a high affinity for carbon, and therefore they are strong carbide formers. These elements are added to improve the oxidation properties of the alloy. The total amount of the elements is up to 1.0 wt%, such as 0.4 wt%, such as up to 0.15.
[0072] The maximum amount of each reactive element will depend primarily on the tendency of that element to form unfavorable intermetallic phases.
[0073] Zirconium (Zr)
[0074] Zirconium is often referred to as a reactive element because it is very reactive toward oxygen, nitrogen, and carbon. In the alloy of the present invention, it has been found that Zr has a dual role in that it will be present in the protective surface layer containing aluminum-rich oxides to improve oxidation resistance, and also forms carbides and nitrides. Therefore, in order to achieve the best properties of the protective surface layer containing aluminum-rich oxides, it is advantageous to include Zr in the alloy.
[0075] However, Zr levels above 0.40 wt% will have an impact on oxidation due to the formation of Zr-rich intermetallic inclusions, and levels below 0.05 wt% will be too small to serve a dual purpose, regardless of the content of C and N. Therefore, if Zr is present, the range is between 0.05-0.40 wt%, such as 0.10 to 0.35 wt%.
[0076] Furthermore, it was found that in order to achieve an even better oxidation resistance of the protective surface layer, i.e. the alumina oxide layer, the relationship between Zr and N and C may be important. Thus, the inventors have surprisingly found that if Zr is added to the alloy and the alloy also contains N and C, and if the following conditions are met (element contents are given in wt. %):
[0077] For example For example The resulting alloy will then achieve good oxidation resistance.
[0078] The balance in a ferritic alloy as defined above or below is Fe and unavoidable impurities. Examples of unavoidable impurities are elements and compounds which are not intentionally added but cannot be completely avoided because they usually occur as impurities in materials used, for example, for the production of ferritic alloys.
[0079] Figure 1a and Figure 1b It is shown that in Si-containing ferritic alloys, higher Cr tends to form Si3Cr inclusions, while 20% Cr also tends to promote the formation of undesirable brittle σ phase after long exposure in the focus temperature region. Although only two Cr levels 10% and 20% are shown in the figure, the trend of increasing brittle phases with increasing Cr level is clearly confirmed. It should be noted that at 10% Cr, there is no σ phase, while at both Cr levels, the amount of Cr3Si phase increases at higher Si content. Therefore, these graphs show that there will be problems when using Cr levels of about 20%.
[0080] When the term "≤" or "less than or equal to" is used in the following context "element ≤ number", the skilled person knows that the lower limit of the range is 0 wt%, unless another number is explicitly stated. Furthermore, the indefinite article "a" or "an" does not exclude a plurality.
[0081] The present disclosure is further illustrated by the following non-limiting examples.
[0082] Example
[0083] The test melt was produced in a vacuum furnace. The composition of the test melt is shown in Table 1.
[0084] The obtained samples were hot rolled and processed into flat bars with a cross section of 2 mm × 10 mm. They were then cut into 20 mm long specimens and ground to 800 mesh with SiC paper to expose to air and combustion conditions. Some bars were cut into 200 mm long × 3 mm × 12 mm bars for tensile testing in a Zwick / Roell Z100 tensile testing apparatus at room temperature.
[0085] The results of the exposure and tensile tests are shown in Table 1.
[0086] The samples were tested for yield and fracture stress and elongation at break in a standard tensile testing machine, and results giving >3% elongation at break were designated as "x" in the "Machinability" column of the table. Thus, "x" indicates an alloy that is readily hot rolled and exhibits ductile properties at room temperature. In the "Oxidation" column, "x" indicates that the alloy forms a protective alumina-rich oxide oxide layer at 950°C in air and at 850°C with biomass ash deposits.
[0087] Table 1 - Melt compositions and results of tests on processability and oxidation
[0088] (x) represents a value between 3% and 6% elongation.
[0089]
[0090]
[0091] Thus, as can be seen from the above table, the alloys of the present disclosure exhibit good machinability and good oxidation properties.
[0092] Figure 2a )to Figure 2e ) discloses a sample, wherein the sample is the present disclosure ( Figure 2a )4783 and Figure 2b )4779) and three comparative alloys after being exposed to biomass (wood chips) ash containing a large amount of potassium at 850°C and exposed for 50 cycles of 1 hour. The micrographs were taken with a JEOL FEG SEM at 1000 times magnification and show the clear performance advantages between the alloys of the present disclosure and the reference materials. It can be seen that on the alloys of the present disclosure, a 3-4μm thin and protective aluminum oxide oxide layer (aluminum oxide layer) has been formed, while a thicker and less protective chromium oxide (chromium oxide) rich oxide layer is formed on stainless steel (2c-11Ni, 21Cr, N, Ce, balance Fe) and Ni-based alloys (2e-Inconel625: 58Ni, 21Cr, 0.4Al, 0.5Si, Mo, Nb, Fe), and a relatively porous and non-protective aluminum oxide oxide layer (aluminum oxide layer) is formed on the comparative FeCrAl alloy (Alloy 4776). Figure 2d -20Cr, 5Al, 0.04Si, balance Fe).
[0093] from Figure 2a-2e It can be seen that the addition of Si, Al and Cr according to the ranges of the present disclosure will promote the formation of an alumina oxide layer at Al levels as low as about 2 wt % and chromium levels as low as 5 wt %.
Claims
1. A ferritic alloy comprising the following elements in weight % [wt %]: C 0.01 to 0.1; N: 0.001 to 0.1; O:≤0.2; Cr 4 to 15; Al 2 to 6; Si 0.5 to 3; Mn: ≤0.4; Mo+W≤4; Y≤1.0; Sc, Ce and / or La=0; Zr 0.05 to 0.40; RE≤1.0; The balance is Fe and normally occurring impurities and must also satisfy the following equation, where the elements are expressed as weight fractions: 0.014≤(Al+0.5Si)(Cr+10Si+0.1)≤0.022, The amounts of C, N and Zr satisfy the following equation:
2. The ferrite alloy according to claim 1, wherein the elements are expressed in weight fractions 0.015≤(Al+0.5Si)(Cr+10Si+0.1)≤0.
021.
3. The ferrite alloy according to claim 1 or 2, wherein Cr is 5-13 wt%.
4. The ferrite alloy according to claim 1 or 2, wherein Cr is 6-12 wt%.
5. The ferrite alloy according to claim 1 or 2, wherein Al is 2.5-4.5 wt% or 3-5 wt%.
6. The ferrite alloy according to claim 1 or 2, wherein Si is 1.0-3 wt%.
7. The ferrite alloy according to claim 1 or 2, wherein Si is 1.5-2.5 wt%.
8. The ferrite alloy according to claim 1 or 2, wherein Zr is 0.10-0.35 wt%.
9. A coating comprising the ferrite alloy according to any one of claims 1 to 8.
10. An article comprising the ferritic alloy according to any one of claims 1 to 8.
11. Use of the ferritic alloy according to any one of claims 1 to 8 for producing coatings and / or coverings and / or articles.
12. Use of a ferritic alloy according to any one of claims 1 to 8 for the manufacture of articles or coatings to be used in corrosive environments.
13. Use of a ferritic alloy according to any one of claims 1 to 8 for the manufacture of articles or coatings to be used in furnaces or as heating elements.
14. Use of a ferritic alloy according to any one of claims 1 to 8 in an environment in which the ferritic alloy is in contact with salts, liquid lead and other metals, in contact with ash or high carbon content deposits, combustion atmospheres, atmospheres with low pO2 and / or high N2 and / or high carbon activity.
Citation Information
Patent Citations
Apparatus and method for detecting fouled cooling circuits in a blast furnace or the like
EP0075420A1
Iron-chromium-aluminium alloy and article and method therefor
EP0091526A2
Rapidly solidified iron-chromium-aluminium alloy foil, with high oxidation resistance
EP0475420A1
Oxidation resistant stainless steel
CA928537A
Iron-chrome-aluminum alloy
CN101090986A